Soil-foundation modelling for vulnerability assessment of buildings in liquefied soils - Maxim Millen (2019)
Recent events have demonstrated that earthquake-induced liquefaction can result in significant structural damage and human casualties. The consideration of soil liquefaction has primarily been the domain of geotechnical engineering; however, recent studies have shown a strong interaction between liquefaction-development and the superstructure loads. Not only does liquefaction lead to a change in the shaking demands on the superstructure, it also changes the flexibility of the soil-foundation-structure system. Meanwhile, the high static shear forces from the foundation loads can result in a reduction or increase in pore pressure development. This strong soil-liquefaction-foundation-structure interaction (SLFSI) is a challenge for both geotechnical and structural engineers. This paper develops an efficient numerical procedure for the vulnerability assessment of buildings with shallow foundations to the combined impacts of seismic shaking and liquefaction. The approach quantifies settlement and soil stiffness as time series to allow SLFSI to be considered in structural modelling in a simplified manner. The time series are developed through a combination of finite difference fully-coupled effective-stress modelling in FLAC and through analytical and empirical expressions based on key parameters. The framework is used to assess the vulnerability of a 3-storey reinforced concrete frame building to liquefaction and ground shaking. (c) 2019 Associazione Geotecnica Italiana, Rome, Italy.